Pengelolaan Operasional Homestay Di Desa Wisata Taro, Kecamatan Tegallalang, Kabupaten Gianyar-Bali - Ida Ayu Kalpikawati; Made Artajaya; Chintia Pinaria (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Taro Tourism Village is one of the rapidly growing tourist villages in Bali. The Hospitality Business Study Program as one of the study programs at the Bali Tourism Polytechnic carries out community service activities in the Taro Tourism Village on March 20 to April 18 2021. The form of Community Service activities for the Hospitality Business Study Program in the Taro Tourism Village is assistance with the theme “Homestay Operational Management in Taro Tegallalang Village, Gianyar”. This activity was attended by 11 participants who are homestay owners and managers in Taro Village, Pokdarwis members and the Taro Village community who want to develop their homes into homestays. Community Service Activities The Hospitality Business Study Program was carried out for 64 hours divided into 9 training sessions. Participants' assessment of the Community Service activities of the Hospitality Business Study Program was that most of the participants considered the material to be very relevant to their needs. All participants stated that after participating in all the activities, they felt that they had gained additional knowledge, insight, and skills in homestay operations.